2021
DOI: 10.1002/pbc.29223
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 in children with cancer in Brazil: Results of a multicenter national registry

Abstract: Background Strategies to mitigate the impact of COVID‐19 in special populations are complex and challenging. Few studies have addressed the impact of COVID‐19 on pediatric patients with cancer in low‐ and middle‐income countries. Methods Multicenter observational cohort study with prospective records and retrospective analyses starting in April 2020 in 21 pediatric oncology centers distributed throughout Brazil. Participants: Patients under 18 years of age who are infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Corso et al. (2021) also noted that from 179 patients they surveyed, the severity of presentation at diagnosis was significantly associated with fatal outcomes (p<0.001); of 22 deaths, 10 patients had leukemia, 2 had lymphoma, and 8 had solid tumors, while 2 patients had other cancer diagnoses ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Corso et al. (2021) also noted that from 179 patients they surveyed, the severity of presentation at diagnosis was significantly associated with fatal outcomes (p<0.001); of 22 deaths, 10 patients had leukemia, 2 had lymphoma, and 8 had solid tumors, while 2 patients had other cancer diagnoses ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…We screened a total of 2759 records after transferring the databases results without duplicates. We further assessed 61 full texts for eligibility which ended up with a total of 21 articles including 14 studies and additional seven studies following manual search procedures 7 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 (Figure 1 , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research papers have identified many factors that can impact the progression of the infection including age, body mass index, co‐infection, neutropenia, initial presentation and the existence of comorbidities. 34 , 51 , 52 Paediatric patients with cancer having low socio‐economic facilities are at greater risk of developing severe COVID‐19 outcomes like hospitalisation and death. This may be related to the precarious nutritional status of children in these countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different international studies have shown that leukemia is one of the most frequent hematology-oncology diseases associated with SARS-CoV-2 infection. 5,7,9,13,14 The reported COVID-19-related mortality rate in pediatric patients with cancer ranges from 0.6% to 4.08%. 7,9,15,16 The impact of the pandemic on the continuity of cancer treatment has been a concern for physicians caring for children and adolescents with cancer.…”
Section: Introductionmentioning
confidence: 99%